A desirable future or unaffordable hope? Queer people becoming parents through assisted reproductive technology (ART) in Guangdong, China. Issue 4 (3rd April 2023) - Tao, Han
Abstract: Based on one-year's ethnographic fieldwork, this article unpacks experiences of assisted reproductive technology (ART) among queer parents and queer wannabe parents in Guangdong, China. Although existing state regulation on the use of ART and birth planning tends to deny parenthood to single and queer people and further limits their ability to form legible family units, queer parents who have had children through ART are growing in number in urban China. This research delineates how state and cultural conventions, together with market and economic conditions, have shaped queer individuals' decision making regarding whether, when and how to have children. Findings make an original contribution to studies of the use of reproductive technology in Chinese queer lives. Narratives regarding how queer parents employ ART services unscramble links between sexual citizenship and reproductive agency, as individuals make consumer choices and reproductive decisions synchronously. The paper also explores alleged LGBT-friendly ART companies and the image of a desirable 'rainbow baby' they have created. Chinese queer parents' participation in assisted reproduction has destabilised the dominant hetero-reproductive family matrix while simultaneously contributing to stratified reproduction.